Growth strategy for Omnia - Stirc, Sever (2016)
This research paper undertakes a qualitative study in order to analyse the current business model of a small company operating in the UK, assess the current strengths and weaknesses and identify options for future growth, together with the changes the company have to undertake in order to succeed. Omnia (CS) Ltd., ‘Omnia” onwards, will be considered as a source and a target for this study, with a concentrated focus on strategizing, as current routine within the pool of activities undertaken by the company. In order to understand, analyse and assess the current level and modalities of strategizing into the company, the logical framework approach will be considered, specific, key elements will be identified and recorded into four different frameworks while interviewing the four key managers, common and different perspectives will be identified and assessed in order to understand where they compete, how they compete and what’s their current selling proposition. An external and internal analysis will be pursued in order to understand the market environment where will they play, identify the important elements to enable them to move further, and suggest what are the capabilities they need in order to succeed, to overcome the disadvantage of being a small company, to leverage the internal, reorganised and reinforced capabilities to project a better outside image, a better business, for a better future.